Unilateral Cleft Lip- Evaluation and Comparison of the Treatment Outcomes Between Two Surgical Techniques Based on Qualitative Assessment - Rudra Joshi 20D04104; Dr. Saikrishna Degala (JSS AHER, Mysuru JSSDCH, Mysuru, 2020)
01. Introduction 02.Aims & Objectives 03.Review of Literature 04.Surgical Anatomy 05.Methodology 06.Case Records 07Results 08.Discussion 09.Conclussion 10.Summary 11.References 12.Annexures